Analisis Sifat Mekanik Komposit Berbahan Tangkai Ilalang Dengan Matriks Polyester Melalui Uji Tarik Untuk Pembuatan Dashboard Mobil - Pratama, Adi; Yuliyanto, Yuliyanto; Subhan, Muhammad (Jurnal Inovasi Teknologi Terapan, 2025)
The use of metals in the industrial world is increasing, so their existence is becoming increasingly rare. This encourages people to think creatively in looking for alternative materials that are easier to obtain and available in abundance, one of which is material made from composite thatch stalks. Composite is a material consisting of two or more materials with different properties combined. This research aims to analyze the effect of thatch stalk lengths of 50, 60, and 70 mm and volume fractions of 35%, 40%, and 45% after soaking the thatch stalks in 4% NaOH solution for 2 hours on tensile tests as an alternative material for making car dashboards. The research results showed that the highest average tensile strength and elastic modulus respectively, namely 26.43 MPa and 9250 MPa, were obtained at a stem length of 60 mm with a volume fraction of 35%. This is caused by the good bond between the resin and the thatch stalks in this variation. This research shows that based on the tensile strength and modulus of elasticity of car dashboards, this research meets the standards.